2016
DOI: 10.1193/121315eqs182m
|View full text |Cite
|
Sign up to set email alerts
|

The Inelastic Input Energy Spectra for Main Shock–Aftershock Sequences

Abstract: This study investigates the input energy spectra for inelastic single-degree-of-freedom (SDOF) systems under main shock–aftershock sequences. The input energy spectra quantitatively reveal the effects of aftershocks on input energy, which verifies the necessity of incorporating aftershocks in energy-based seismic design. The investigation selects the sequences including one aftershock or two aftershocks respectively, according to the proposed criteria for selecting earthquake records. Then, the input energy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 37 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…Especially, nonlinear single degree of freedom (SDOF) systems subjected to MSAS sequences were used in Refs. [1][2][3][4][5][6] and both global and local damage indices accounting for energy dissipation [7] were found to be highly sensitive in the MSAS seismic records. Contrarily, no sound influence was corroborated on deformations-based indices including the maximum and residual displacement as well as displacement ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, nonlinear single degree of freedom (SDOF) systems subjected to MSAS sequences were used in Refs. [1][2][3][4][5][6] and both global and local damage indices accounting for energy dissipation [7] were found to be highly sensitive in the MSAS seismic records. Contrarily, no sound influence was corroborated on deformations-based indices including the maximum and residual displacement as well as displacement ductility.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the ASs could lead to a significant increase in structural inelastic deformation and energy dissipation. After that, various structural performance indicators, e.g., peak displacement response [5][6][7], behavior factor [8,9], ductility demand [8,[10][11][12][13], input energy [14], damage index [15], and collapse capacity [16], have been adopted to examine the AS effect by subjecting SDOF systems to a suite of real [11,12] or artificial [8][9][10][11]15,16] MS-AS sequences. Recently, multiple degree of free dom systems (MDOFs) have been used to investigate the structural damage caused by MS-AS sequences; the studied structures include steel frames [17] bare and infilled reinforced concrete frames [18][19][20], wood structures [21], equipped structures [22], bridges [23] and other kind of structure [24].…”
Section: Introductionmentioning
confidence: 99%
“…Ruiz‐García, [ 2 ] Goda, [ 3 ] and Goda et al [ 4 ] studied the differences in characteristics between a mainshock and major aftershock records, providing useful insights into the MSAS records selection or generation. The response spectra of MSAS sequences were proposed for the performance evaluation [ 5–9 ] and seismic design [ 10–14 ] after considering the effects of aftershocks. The influence of MSAS sequences on the seismic response of buildings, mainly including steel frames [ 15–18 ] and reinforced concrete (RC) frames, [ 19–21 ] was also investigated with recorded or artificial MSAS sequences.…”
Section: Introductionmentioning
confidence: 99%